HCV GENOTYPES AND ITS ASSOCIATION WITH RESPONSE TO TREATMENT - Aftab Ahmad Khan; Naghmi Asif; Rizwan Uppal; Gul E Rehan (Journal of University Medical & Dental College, 2020)
BACKGROUND & OBJECTIVE: primary Hepatitis C is a serious public health problem and is the cause of liver cirrhosis, hepatocellular carcinoma (HCC), and numerous end-stage liver disease manifestations. The management of hepatitis C is to preclude liver cirrhosis, lessen the risk of hepatocellular carcinoma or hepatoma, and curing the extra hepatic diseases. Initially, interferon was the cornerstone for treating hepatitis C, but due to its cumbersome complications, route of administration, and limited treatment access, many patients showed noncompliance. New therapies for chronic hepatitis C have been introduced based on direct antiviral eﬀects. Several genotypes of hepatitis C have been discovered and they are responsive to diﬀerent antiviral therapies. Our objective was to assess the genotypic distribution of HCV in our local setup and their pattern of response to diﬀerent combination of anti-viral therapies by assessing the sustained viral response (SVR) after 12 weeks post-treatment. To determine the most prevalent genotype of hepatics C virus in our population and pattern of the response of multiple genotypes to diﬀerent antiviral regimens.METHODOLOGY: It is a cross-sectional study conducted for duration of six months and recruited those patients whose polymerase chain reaction (PCR) was found positive for hepatitis C virus at Islamabad Diagnostic Center. We analyzed 100 patients, both children and adults. Patients were assessed for diﬀerent genotypes and then diﬀerent combinations of antiviral treatments were administered. Their clinical data, hematological parameters and viral load before and after treatment were also analyzed.RESULTS: In a total of 100 positive hepatitis C virus-infected patients, 55% were females and 45% males. The frequencies of genotypes observed were 91 %, 06%, and 03% of genotype 3, 1a, and 1b respectively. 51 out of 91 patients with type 3 genotype, who were on antiviral therapy of sofosbuvir and ribavirin, all of them achieved SVR. 30 out of 91 patients with type 3 genotype were treated with sofosbuvir alone, the percentage of failure to achieve SVR in them was 6.7%. Treatment failure percentage of 10% was observed when a combination of Interferon (INF) alpha and ribavirin was used in type 3 genotype. Remaining six patients with type 1a and three patients of type 1b genotype achieved SVR with diﬀerent regimens used.CONCLUSION: Although the increased load of HCV in our setup is an alarming situation the prevalence of type 3 genotype is a blessing in disguise. The success of sustained viral response after various combinations of direct antiviral therapy and interferon-free treatment is hope for the ultimate cure of the disease and avoidance of debilitating side eﬀects related to interferon.